Innovative Supply Chain in Italian Knitwear Industry. The Case of Medium-Sized Firms - Maria Rosaria Marcone (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
This paper aims to provide the empirical evidence of the interaction mechanism in the open innovation system with particular attention to aesthetic and rational innovation in an Italian creative sector. Factors including rapid technological development, the advent of innovative openness processes involving sub-sectors belonging to diversified supply chains, shorter product life cycles, more diversified and customized, demande and fierce marketing competition, make today's business model increasingly unpredictable and risky. Building on relational based view, resource-based view and network analysis the purpose of this paper is to empirically explore the relationships among supply chain integration (SCI) and inter-company performance in global diversified supply chain. This is an exploratory study and the qualitative research method has been employed. This research has founded its context in the Italian knitwear sector which is part of the creative industries of the Italian fashion system. The data were collected through a series of semi-structured interviews with workers belonging to various areas of activity and with external actors such as yarn suppliers, buyers, institutional and non-institutional lenders. The purpose of this research is also to promote research methodological approaches to analyse different uncertainty scenarios for the future.
Keywords: 650; innovative openness processes; innovative manufacturing systems; supply chain integration